(untitled) (Scientific journal of the Fergana State University, 2025)
The list of species and subspecies registered in the Fergana Valley, along with their higher taxa, is presented. It has been established that 20 species and 7 subspecies of longhorn beetles are distributed in the Fergana Valley, belonging to 5 subfamilies, 15 tribes, 20 genera, and 11 subgenera. To determine the species composition of longhorn beetles in the region, internationally recognized catalogs such as the “Titan database on Cerambycidae or Longhorn beetles” (http://titan.gbif.fr/index.html), “Lamiines of the World” (https://lamiinae.org/about.html), “Cerambycidae: Subfamily Prioninae of World” (http://www.cerambycidae.cz/home-page.html), “Catalogue of Palaearctic Chrysomeloidea (Vesperidae, Disteniidae, Cerambycidae)” (http://www.cerambycidae.net/), as well as the extensive scientific literature contained in these sources, were used. In addition, the study is based on samples collected from over 30 locations in the Fergana Valley from 2012 to 2023.